Duchowieństwo patriotyczne – aspekt historyczno-pastoralny - Myszor, Jerzy (Studia Pastoralne, 2026)
The article shows various expressions of patriotism and its relationship to nationalism in historical terms. There are two non-competing definitions of patriotism issued in Polish public discourse. The first one presupposes accompanying and even participation in military resistance against an outside enemy, the second consist in organic work – that is in grass-root activities. The Polish Catholic Clergy actively participated in both national uprisings and in organic work. Nowadays the Polish Catholic Clergy plays a role of a memory organizer within a framework of unifying Europe and its tendency to forget or even blot out its history.